Effect of Indole Butyric Acid Concentrations on Rooting of the Green and Hard-Wood Cuttings of Some Plum Clone Rootstocks - Ozkan, Yakup; Arslan, Atilla; Gercekcioglu, Resul; Gunes, Mehmet (Asian Journal of Chemistry, 2016)
The studies of rooting situations of the green and hardwood cuttings of clonal plum rootstocks such as Myrobalan GF-31, Marianna GF-8-1, Myrobalan B and Commen Mussel were carried out. For green cuttings hormone concentrations of 0, 2000, 4000 and 6000 ppm of indole butyric acid (IBA) were used whereas for hardwood cuttings hormone concentration of 0, 1000, 2000 and 4000 ppm of IBA were used. The callusing ratio, average number of roots, average length of roots, root quality, practical cutting ratio at plant production and active cutting ratio were investigated. The highest rooting ratio was obtained as 95% in the green cuttings of Myrobalan GF-31 and 87.50% in the hardwood cuttings of Marianna GF-8-1 were found better than Myrobalan B and Commen Mussel.